The role of lifestyle and diet in the course of cataract: a literature review - Wydrych, Andrzej; Domański, Andrzej; Dziekońska, Małgorzata; Wójcik, Martyna; Kowalczyk, Klaudia; Bogiel, Zofia; Machała, Antonina; Tomczyk, Aleksandra (Quality in Sport, 2026)
Introduction: Cataract, a progressive and largely irreversible opacification of the lens, remains a leading cause of visual impairment and blindness globally, with significant medical, social, and economic consequences. While aging is the main risk factor, lifestyle and environmental factors also influence cataract development. Aim: This review examines current evidence on the role of lifestyle, diet, and environmental exposures in the onset and progression of cataract, with a focus on identifying modifiable determinants that may inform preventive strategies. Materials and methods: For this review, we searched databases such as PubMed and Google Scholar using “cataract”, “diet”, “triggers”, “relationship”, “solar radiation”, “smoking”, and “alcohol”. We cited twenty-three articles in this publication. The review covers studies from 1966 to 2025. Results: Epidemiological and clinical studies indicate that diet quality, smoking, alcohol consumption, ultraviolet (UV) exposure, and corticosteroid use affect cataract risk. Diets rich in fruits, vegetables, antioxidants, and healthy fats are protective, while smoking and alcohol intake consistently increase risk. Corticosteroid use is strongly associated with posterior subcapsular cataracts, and cumulative UV exposure, along with environmental stressors such as heat and low humidity, contributes to regional disparities in disease burden. Conclusions: Cataract is a multifactorial condition influenced by aging, lifestyle, environmental, and pharmacological factors. Targeting modifiable risk factors through diet, lifestyle interventions, UV protection, and cautious corticosteroid use represents a crucial public health strategy. Future longitudinal, interventional, and epidemiological studies are warranted to clarify causal pathways and interactions, providing a robust evidence base for effective preventive programs aimed at delaying cataract onset.